2017
DOI: 10.3899/jrheum.170449
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Disease Activity as a Treatment Target in Psoriatic Arthritis: A Review of the Literature

Abstract: As in other inflammatory rheumatic diseases, the objective of psoriatic arthritis (PsA) treatment is the achievement of a defined target. Recent recommendations propose aiming for remission or low disease activity; however, a consensual definition of remission is lacking. A state of minimal disease activity (MDA) has been established and is defined by low activity assessed by tender/swollen joint counts, tender entheseal points, Psoriasis Area and Severity Index or body surface area, patient pain and global ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 45 publications
2
69
0
4
Order By: Relevance
“…After 2 years of protocol‐driven, treat‐to‐target therapy, the proportion of patients achieving MDA increased from 16.7% at baseline to 63.3% at 12 months and to 68.9% at 24 months. The proportion of patients achieving MDA in our cohort at months 12 and 24 was similar to that in other observational studies in patients treated with anti‐TNF agents (44–64%) . A previous studies demonstrated that 60% of patients had achieved MDA on at least 1 visit and 34% had achieved MDA on consecutive visits for at least 12 months , which is similar to the results from the current study (55% and 46%, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…After 2 years of protocol‐driven, treat‐to‐target therapy, the proportion of patients achieving MDA increased from 16.7% at baseline to 63.3% at 12 months and to 68.9% at 24 months. The proportion of patients achieving MDA in our cohort at months 12 and 24 was similar to that in other observational studies in patients treated with anti‐TNF agents (44–64%) . A previous studies demonstrated that 60% of patients had achieved MDA on at least 1 visit and 34% had achieved MDA on consecutive visits for at least 12 months , which is similar to the results from the current study (55% and 46%, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…In some cases, enthesopathy represents the initial and predominant manifestation in conditions such as the seronegative spondyloarthropathies (SpAs) . Enthesitis is common in SpA patients and occurs in synovial joints, the Achilles tendon enthesis, the plantar fascia and other sites …”
Section: Introductionmentioning
confidence: 99%
“…2,3 In some cases, enthesopathy represents the initial and predominant manifestation in conditions such as the seronegative spondyloarthropathies (SpAs). 4 Enthesitis is common in SpA patients and occurs in synovial joints, the Achilles tendon enthesis, the plantar fascia and other sites. [4][5][6] MRI has been widely used for visualizing the features of arthritis and traumatic disease, 6 but conventional clinical MRI has not been helpful for demonstrating and characterizing the key normal tissues present in tendons and entheses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After the creation of the PsAID-12, it became also important to verify how this instrument, a disease impact measure, is related the disease activity measures to understand its usefulness in clinical practice (17). Currently, a range of composite indices is available to assess disease activity in PsA, and there is no consensus on which is best, since each has specific advantages and limitations. However, MDA (Minimal Disease Activity) stands out among them, since it is a simple, easy-to-use index that covers a greater number of PsA domains, including skin, and mainly because it has been applied as a target for treatment decision making (18).…”
Section: Introductionmentioning
confidence: 99%